2016
DOI: 10.1103/physreve.93.062418
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitivity and noise amplification in a model ofV. harveyiquorum sensing

Abstract: We analyze ultrasensitivity in a model of Vibrio harveyi quorum sensing. We consider a feedforward model consisting of two biochemical networks per cell. The first represents the interchange of a signaling molecule (autoinducer) between the cell cytoplasm and an extracellular domain and the binding of intracellular autoinducer to cognate receptors. The unbound and bound receptors within each cell act as kinases and phosphotases, respectively, which then drive a second biochemical network consisting of a phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…For non-oscillatory QS systems, it would be interesting to use the intracellular Lux-signaling pathways of [32] into our PDE-ODE model (1.0.1) to analyze sudden jumps between small and large amplitude steady-states for bistable QS systems as the cell density increases past a saddle-node bifurcation value. Moreover, (1.0.1) can be used to study the effect of spatial diffusion on the parallel QS signaling pathways associated with the marine bacterium V. harveyi, which were recently modeled in [5] through an ODE well-mixed limit. Our analysis in §3 has shown that the dimensionless PDE-ODE system (1.0.2) can be reduced to a limiting ODE system only when the bulk diffusivity satisfies D = O(− log ε), where ε is the dimensionless ratio of the cell radius to the length scale of the domain.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…For non-oscillatory QS systems, it would be interesting to use the intracellular Lux-signaling pathways of [32] into our PDE-ODE model (1.0.1) to analyze sudden jumps between small and large amplitude steady-states for bistable QS systems as the cell density increases past a saddle-node bifurcation value. Moreover, (1.0.1) can be used to study the effect of spatial diffusion on the parallel QS signaling pathways associated with the marine bacterium V. harveyi, which were recently modeled in [5] through an ODE well-mixed limit. Our analysis in §3 has shown that the dimensionless PDE-ODE system (1.0.2) can be reduced to a limiting ODE system only when the bulk diffusivity satisfies D = O(− log ε), where ε is the dimensionless ratio of the cell radius to the length scale of the domain.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Derive the contraction theory [2,27,28]. In general, we are considering dimension dynamical system: = ( , ), ∈ ℝ (1) Here, map : ℝ → ℝ is smooth nonlinear vector field, we then can define norms for vector and matrix and A.…”
Section: Global Convergencementioning
confidence: 99%
“…Quorum sensing [2][3][4] is important systematic stimulus and response that is sensitive to population density of interest. Functionally, ant is using quorum sensing to coordinate behaviors including foraging [5], house hunting [6,7], and cooperative transport [8].…”
Section: Introductionmentioning
confidence: 99%
“…These linear equation can be analyzed along similar lines to the single-cell case using Fourier transforms and contour integration [55]. Here, we simply state the final results (for large N ).…”
Section: 32mentioning
confidence: 99%